2015
DOI: 10.7196/samj.9649
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the administration of antibiotics in critically ill patients

Abstract: Optimal outcome and a reduction in the potential for resistance require that appropriate pharmacokinetic (PK) targets are achieved. Consequently, we need to target drug concentrations that are significantly higher than those conventionally presumed to be adequate.Drug exposure varies according to the molecular weight, degree of ionisation, protein binding and lipid solubility of each agent. In critically ill patients, hypoalbuminaemia increases the free fraction of hydrophilic drugs, which in turn increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…This demonstrates a lack of understanding regarding the need for appropriate loading doses, which should be in the region of 9 -12 MU regardless of renal function. [9,19] The findings of our study further emphasise the importance of ensuring optimal dosing as, although Acute Physiology and Chronic Health Evaluation II (APACHE II) scores were not available so that patients could be appropriately matched, higher loading doses appeared to be associated with shorter duration of treatment. Interestingly, there also appeared to be an association with the manner in which the maintenance doses were administered.…”
Section: Discussionmentioning
confidence: 83%
“…This demonstrates a lack of understanding regarding the need for appropriate loading doses, which should be in the region of 9 -12 MU regardless of renal function. [9,19] The findings of our study further emphasise the importance of ensuring optimal dosing as, although Acute Physiology and Chronic Health Evaluation II (APACHE II) scores were not available so that patients could be appropriately matched, higher loading doses appeared to be associated with shorter duration of treatment. Interestingly, there also appeared to be an association with the manner in which the maintenance doses were administered.…”
Section: Discussionmentioning
confidence: 83%
“…The rationale for higher doses is related to the lower than expected drug concentrations in critically ill patients. 20 Plasma concentrations of hydrophilic antibiotics may be decreased owing to the increased volume of distribution due to capillary leak, the reduced albumin (for highly protein bound drugs) and fluid overload. In addition augmented renal clearance (ARC) due to increased cardiac output from use of inotropes, and renal replacement therapy 21 may contribute.…”
Section: Daily Dose Of Antibioticsmentioning
confidence: 99%
“…Thursky et al 24 found that the implementation of a computerised system, incorporating the microbiology and a decision system, assisted in reducing the use of unnecessary broad-spectrum agents. Similarly, obtaining timeous and appropriate specimens prior to initiating antibiotic treatment is critical 20 in ensuring the correct antibiotic choice and facilitating de-escalation. In CMJAH future studies need to be cognisant of these fundamental principles.…”
Section: Study Limitations and Further Recommendationsmentioning
confidence: 99%
“…9 Efek antibakteri yang optimal dari antibakteri concentrationdependent bergantung pada luas area di bawah kurva penghambatan yang disederhanakan menjadi rasio antara konsentrasi optimal bila dibanding dengan MIC antibakteri tersebut. 10 Pada penelitian ini diketahui efek antibakteri paling optimal dihasilkan pada konsentrasi 39,06 ppm. Hal ini belum dapat dipastikan karena pada penelitian ini pengujian konsentrasi di atas 39,06 ppm, yaitu pada konsentrasi 78,13 ppm dipengaruhi oleh sifat kekeruhan yang dimiliki oleh ekstrak kasar sehingga perhitungan persentase kematian sel bakteri tidak dapat dilakukan.…”
Section: Gambar 3 Grafik Perbedaan Persentase Kematian Sel Antara Konunclassified